2020
DOI: 10.1177/0308022620954117
|View full text |Cite
|
Sign up to set email alerts
|

The use of everyday technology; a comparison of older persons with cognitive impairments’ self-reports and their proxies’ reports

Abstract: Introduction Older persons with cognitive impairment have often been disregarded in providing information on their own perceptions. This study explored the number of relevant everyday technologies and the ability to use everyday technologies as perceived by persons with cognitive impairment in comparison with their proxies’ estimates using the Short Everyday Technology Use Questionnaire. Method In this cross-sectional study, persons with cognitive impairment ( n = 21) and their proxies ( n = 21) were interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Providing such information is, thus, one way to enhance feelings of safety and security in older persons receiving home care services. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing such information is, thus, one way to enhance feelings of safety and security in older persons receiving home care services. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Older persons whose needs are met by home care services have been reported to experience better psychosocial and general well-being than those with unmet needs. 13 Although the older person is best qualified to give a perspective on their care needs, 16–18 in research, their views are often represented by others, such as relatives or health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this research was a questionnaire survey based on information provided by family members of the older adults. Older adults with SMC or MCI may perceive everyday management changes sooner than family members [13, 35] and indicate higher matching with observation assessment [15]. Self-reporting of difficulties with ET and refrigerator management are important sources of information in individual contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been suggested that decline in the ability to use ETs may predict diminishment in accomplishing social and complex everyday activities due to MCI [12]. Older adults with MCI were accurately aware that their ability to use ETs was declining [13][14][15]. Older adults recognize their MCI leads to inefficient use of ETs and more efforts required to maintain everyday life, as the ability to use ETs has become a prerequisite for using services in public spaces (ticket machines and ATMs).…”
Section: Introductionmentioning
confidence: 99%
“…Within the population groups that have been affected by this digitalization, the existing digital gap in the older adult population is remarkable; in addition, even within the same group, differences have been identified between those who suffer from a cognitive impairment and who live in rural areas, among other factors [ 10 , 11 ]. Mild cognitive impairment (MCI) represents a transitional state between healthy aging and very mild Alzheimer’s disease (AD), involving a cognitive decline which is greater than expected for that age [ 12 ].…”
Section: Introductionmentioning
confidence: 99%